2015
DOI: 10.1007/jhep10(2015)167
|View full text |Cite
|
Sign up to set email alerts
|

Bubbling geometries for AdS2× S2

Abstract: We construct BPS geometries describing normalizable excitations of AdS 2 ×S 2 . All regular horizon-free solutions are parameterized by two harmonic functions in R 3 with sources along closed curves. This local structure is reminiscent of the "bubbling solutions" for the other AdS p ×S q cases, however, due to peculiar asymptotic properties of AdS 2 , one copy of R 3 does not cover the entire space, and we discuss the procedure for analytic continuation, which leads to a nontrivial topological structure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 111 publications
0
21
0
Order By: Relevance
“…In particular, consistent with the example in [10] mentioned above, 4-dimensional spacetimes that satisfy the ANEC strictly could not have AdS 2 × S 2 asymptotics. All of this suggests that the examples constructed in [7] cannot be globally regular, which, in fact, has since been confirmed by Lunin [9].…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…In particular, consistent with the example in [10] mentioned above, 4-dimensional spacetimes that satisfy the ANEC strictly could not have AdS 2 × S 2 asymptotics. All of this suggests that the examples constructed in [7] cannot be globally regular, which, in fact, has since been confirmed by Lunin [9].…”
Section: Introductionmentioning
confidence: 63%
“…[10] and references therein. More recently a class of horizon free supersymmetric solutions to Einstein-Maxwell theory having AdS 2 × S 2 asymptotics has been constructed by Lunin [7]. However, on the basis of an example considered in [10,Section 2.2], and also a result in [5] (Theorem 2.1), Maldacena has suggested that any asymptotically AdS 2 × S 2 spacetime that obeys the null energy condition (NEC), or more generally the average null energy condition (ANEC), should be quite special.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most recent frontiers seems to be the Type II AdS 2 × S 2 × T 6 background with R-R fluxes, preserving 8 supersymmetries [9][10][11][12][13]. The holographic dual is either expected to be a superconformal quantum mechanics, or a chiral 2D CFT [14][15][16][17] (see [18][19][20][21][22][23][24][25][26][27][28][29] for recent work).…”
Section: Introductionmentioning
confidence: 99%
“…They belong to the so-called IWP family of solutions [57,58] and are characterized by one complex harmonic function in three dimensions. The main differences between the solutions in [55] and ours are as follows. First, because the solutions in [55] are based on one complex harmonic function, their possible monodromies are Abelian.…”
Section: Implication For Black-hole Microstatesmentioning
confidence: 89%